Atypical Anchoring of Gingival Epithesis - Z. Kadlec (Czech Dental Chamber, 2008)
Then paper demonstrates the treatment 16 year female patient who suffered an injury consisting of teeth 13, 12, 11 and 21 luxation and loss-making fracture of alveolar process of upper jaw by means of dental implants, fixed bridge and silicon gingival epithesis. The unfavorable position of implant fixtures leading tit be formation of an atypical construction of fixed bridge was solved by a special retention device of gingival epithesis the authors suggested.